Viral Profile and Clinical Characteristic in Acute Asthma Exacerbation Patients - Resti Yudhawati; Erwin Winaya; Laksmi Wulandari; Aldise M Nastri; Retno A Setyoningrum; Kazufumi Shimizu (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Asthma is a heterogeneous disease characterized by chronic airway inflammation. Thevirus infection in respiratory tract will activate greater pro-inflammatory cytokines in asthma patients.The enhancement of pro-inflammatory cytokines induces various clinical symptoms. This study aims toinvestigate the respiratory virus and clinical characteristics among patients with acute asthma exacerbation.Methods: In this study, subjects were divided into 3 groups based on acute asthma exacerbation triggers.The first group triggered by virus infection; the second group triggered by non-virus infection with ILI; andthe third group without any infection. Nasopharynx or throat swabs were collected to detect any respiratoryvirus. Virus was detected by Multiplex PCR (xTAG Respiratory Viral Panel Fast V2/ LUMINEX)Results: According to PCR examination, the prevalence of virus infection was 46.2%. Only two types ofviruses identified, which were Influenza A virus and Rhinovirus. All patients in the second groups showeda symptom of cough with purulent sputum, while no patients from the other two groups showed similarsymptoms. PEFR and % PEFR prediction of patients with Influenza A virus infection were higher than inRhinovirus infected-patients (210 L/min and 48.6% vs 195 L/min and 45%).Conclusion: Acute asthma exacerbation is one of the most reasons patients came to emergency ward. Themajority of acute asthma exacerbation was caused by infection, and most of it was viral infection. Clinicalsign differs according to the trigger, therefore the use of antibiotics should be avoided, unless there are signsand symptoms of bacterial infections